Hubungan Antara Kecerdasan Emosi Dengan Prestasi BElajar Pada Siswa Kelas VII Di SMP N 1 Sambong Kabupaten Blora - Sri Aryati, Fahmi; , Drs. Daliman, S.U (2015)
An education, learning becomes a way of demonstrating a positive change to later obtain new skills and knowledge. Learning the needs of all people, because by studying a person can understand or master something that ability can be improved. In studying and adjusting an existing lesson in school, many junior high school students who face all the problems on himself that demands time, energy and mind of students. Suppose on existing activities within the scope of school subjects, extracurricular activities and other general activities and the student must adapt himself to the school and outside the school environment. This must be balanced so that students can achieve better academic achievement. Learning achievement is influenced by two factors: internal and external factors. Factors include 1) the physical body which health factors, 2) psychological, namely intelligence (EQ and IQ), attention, interest, talent motives, maturity, readiness and self efficacy. If intelligence is high then the student learning achievement is high, and vice versa. The main objective of this research was to determine the relationship between emotional intelligence and academic achievement in class VII SMP N 1 Sambong Blora. The hypothesis is the existence of a positive relationship between emotional intelligence and academic achievement of students of class VII in SMP N 1 Sambong Blora. Research subjects are students of class VII A, VII B and VII C SMP Negri 1 Sambong responden.Teknikpengambilan totaling 100 samples using population studies. Data collection tools used intelligence scale emosidanpengambilan average results of students in the semester report cards 1. Methods of data analysis using nonparametric Spearman's correlation technique rho. Based on nonparametric analysis obtained correlation coefficient (r) of 0,270; p = 0.003 (p <0.01). The results showed there was a significant positive correlation between emotional intelligence and academic achievement, and vice versa very significant negative relationship between emotional intelligence, the lower the learning achievement. Emotional intelligence effective contribution to the learning achievement of 7.29% .Kecerdasan emotions have empirical mean sebesar109,79dan hypothetical mean that berartikecerdasan 92.5 emotion is high. While the variable learning achievement has the empirical mean (RE) of 3.13509 and the average hypothetical (RH) of 284.25, which means emotional intelligence on the subject was moderate.